The Queen of the Pirate Isle - Harte, Bret, 1836-1902 (Salt Lake City, UT : Project Gutenberg, 2006)
"The Queen of the Pirate Isle" by Bret Harte is a children's story written in the late 19th century. This whimsical tale follows the imaginative adventures of a young girl named Polly, who accidentally becomes the queen of a pirate band formed by her friends during a game in their nursery. The book delves into themes of childhood imagination, play, and the blurring of reality and fantasy. In the story, Polly and her companions, Hickory and Wan Lee, engage in elaborate games of make-believe, with Polly assuming the role of their pirate queen. Their adventures lead them to create elaborate narratives filled with pirate escapades, imaginary captures, and playful conflicts. The climax occurs when they stumble upon a cave that houses a group of miners disguised as pirates, leading to unexpected revelations about friendship, bravery, and the nature of their games. Ultimately, the story portrays the innocence and creativity of childhood while highlighting the depth and complexity of young imaginations. (This is an automatically generated summary.)
There is an improved edition of this title, eBook #17168
Wikipedia page about this book: https://en.wikipedia.org/wiki/Portal:Children%27s_literature/Selected_picture/4
Release date is 2006-03-27
Produced by Donald Lainson; David Widger
Keywords: American fiction -- 19th century; Pirates -- Juvenile fiction; Fantasy games -- Juvenile fiction; Gold mines and mining -- California -- Juvenile fiction; Stanislaus River (Calif.) -- Juvenile fiction